Kontroversi Penggunaan Permainan Bahasa dalam Komunikasi Antarbudaya di Pesantren Multietnis - Musyarrafah, Musyarrafah; Nurhayati, St; Syafri Idris, Andi Muhammad (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
The aim of the study is to analyze the implementation of Ludwig Wittgenstein’s language games theory in the context of intercultural communication at Pondok Pesantren Manahilil Ulum DDI Kaballangan. This research was employed a qualitative approach with participatory observation and in-depth interviews. Data were collected from utterances of students from various ethnic backgrounds, such as Buginese, Mandarese, Makassarese, and Pattinjonese, with two informants from each ethnic groups, to understand how differences in word meanings affect communication dynamics. The findings show that the different language games in each ethnic group’s local language cause significant misunderstandings, as seen in words like “bosi,” “buto,” and “doko.” However, these misunderstandings were resolved through communication adaptations, such as the use of Indonesian as a bridging language. The originality of this study lies in the application of language games theory in a multi-ethnic boarding school setting, which has not been extensively explored in the context of education. This research provides new insights into the dynamics of intercultural communication in boarding school and the adaptive strategies used by students to maintain harmony. The study’s implications highlight the importance of cross-cultural awareness and the appropriate use of language to enhance communication effectiveness in multi-ethnic boarding school settings